The creep of alloy 617 at 700 °C: Material properties, measurement of strain and comparison between finite element analysis and digital image correlation. (15th December 2017) - Narayanan, A.; Dubey, K.; Davies, C.M.; Dear, J.P.
Highlights: Specimens of Alloy 617 have been tested at 700 °C to evaluate creep properties. Creep of the alloy in multiaxial conditions is assessed Digital Image Correlation. An FE model based on power law creep model is compared to real behaviour. The model shows agreement with experimental evidence. Abstract: Future generations of power plants, such as the Ultra-Super-Critical (USC) power plants, are being designed to be operated at more extreme pressures and temperatures in order to achieve higher efficiency. One candidate material for components is Inconel alloy grade 617, a nickel based superalloy, which is expected to possess better creep resistance in comparison to other types of alloys (Bhadeshia and Honeycombe, 2011; Evans and Wilshire, 1993 ). At present there is little available data or information about the behaviour of this material at the temperature of interest (700 °C) and hence there is a need to evaluate its properties under these conditions. This paper details experimentation on Alloy 617 to evaluate its uniaxial behaviour under tension and creep at 700 °C, using the results obtained to develop a creep damage model based on power law creep in conjunction with the Cocks–Ashby void growth approach Cocks and Ashby (1982) for creep in a multiaxial stress state. Finite Element (FE) simulations are compared to experimental results obtained by Digital Image Correlation (DIC), which is used in order to validate the effectiveness of a power law creep damage model. Results made using a novel electrical strain sensor using ACPD principles supplement this work to draw comparisons between the response of the sensor and the strain field experienced by the specimen.